Insights into the expanding phenotypic spectrum of inherited disorders of biogenic amines - Oya Kuseyri Hübschmann (Nature Portfolio, 2021)
Inherited disorders of neurotransmitter metabolism represent a group of rare neurometabolic diseases characterized by movement disorders and developmental delay. Here, the authors report a standardized evaluation of a registry of 275 patients from 42 countries, and highlight an evolving phenotypic spectrum of this disease group and factors influencing diagnostic processes.